Menumbuhkan Minat Melanjutkan Studi Ke Perguruan Tinggi Siswa Sekolah Menengah Kejuruan (SMK) Perpajakan - Reni Farwitawati; Masirun Masirun (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Through the Community Service Program (PKM) to create an additional learning platform by providing explanations or seminars and motivation to be precise is motivation leadership about how to generate potential from within students and about how to motivate students to continue their education. at University. It is hoped that a good level of education and adequate skills can improve the quality of human resources so that development can run well too. The method of implementing this activity is by lecturing. The result of this activity is the increasing interest of students of SMK Taxation Riau to continue their higher education, this can be seen from the results of the post test and pre test given to the participants of the activity.